E–COMMERCE BISNIS DAN INTERNET - Dasopang, Nursania (STAI Darul Qalam Tangerang, 2024)
E-Commerce is any form of trade transaction for goods or services using electronic media. The electronic media discussed here is only focused on the use of internet media. The objectives of this study are 1) to describe the history of development and forms of e-commerce and 2) to decrypt the Islamic view of e-commerce. This research is a library research (library reseach. Data is obtained by reviewing the literature literature. Research findings describe that in 1970, Electronic Fund Transfer (EFT) emerged whose application at that time was limited to well-known companies. Next is Electronic Data Interchange (EDI). The rapid development of technology in the 90s, e-commerce applications from various companies emerged so that commercialization occurred. There are several forms of e-commerce, namely: Business to Consumer (B2C), Consumer to Consumer (C2C), classified ads, e-commerce shopping malls and Online to Offline (O2O). The basis for e-commerce negotiations can be based on the main maslahah, namely quoting the benefits and encouraging the success in fulfilling the target of sharia